EXPERIMENTAL CONSTRAINTS ON VOLATILE ABUNDANCES IN ARC MAGMAS AND THEIR IMPLICATIONS FOR DEGASSING PROCESSES - Scaillet B.; Pichavant M. (My University, 2003)
Recent phase equilibrium studies, combined with analytical and petrological data, provide rigorous constraints on the pre-eruptive P-T-fH(2)O-fO(2)-fS(2)-fCO(2) conditions of silicic to mafic arc magmas. Pre-eruptive melts show a broad negative correlation between temperature and melt H(2)O contents. Pre-eruptive melt S contents cluster around 100 ppm in residual rhyolitic liquids of silicic to andesitic magmas, and range up to 5000 ppm in more mafic ones. For the entire compositional spectrum, melt sulphur contents are almost independent of prevailing fO(2). In contrast, they are positively correlated to fS(2), in agreement with experimental observations. Using these intensive constraints, the composition of coexisting fluid phases has been modelled through a MRK equation of state. Pre-eruptive fluids in silicic to andesitic magmas have XH(2)O (mole fraction of H(2)O) in the range 0.65-0.95. XH(2)O decreases as pressure increases, whereas XCO(2) increases tip to 0.2-0.3. Pre-eruptive fluids in hydrous mafic arc magmas, such as high-alumina basalts, generally have similar mole fractions of H(2)O and CO(2) at mid-crustal levels, with XH(2)O increasing only for magmas stored at shallow levels in the crust (<1 kbar). The sulphur content of the fluid phase ranges from 0.12 up to 6.4 wt% in both mafic and silicic magmas. For silicic magmas coexisting with 1-5 wt% fluid, this implies that more than 90% of the melt+fluid mass of sulphur is stored in the fluid. Calculated partition coefficients of S between fluid and melt range from 17 up to 467 in silicic to andesitic magmas, tending to be lower at low fO(2), although exceptions to this trend exist. For mafic compositions, the sulphur partition coefficient is constant at around 20. The composition of both melt and coexisting fluid phases under pre-eruptive conditions shows marked differences. For all compositions, pre-eruptive fluids have higher C/S and lower H/C atomic ratios than coexisting melts. Comparison between volcanic gas and pre-eruptive fluid compositions shows good agreement in the high temperature range. However, to reproduce faithfully the compositional field delineated by volcanic gases, silicic to andesitic arc magmas must be fluid-saturated under pre-eruptive conditions, with fluid amounts of at least 1 wt%, whereas mafic compositions require lower amounts of fluid, in the range 0.1-1 wt%, Nevertheless, volcanic gases colder than 700degreesC are generally too H(2)O-rich and S-poor to have been in equilibrium with silicic to andesitic magmas tinder pre-eruptive conditions, which suggests that such gases probably contain a substantial contribution from meteoric or hydrothermal water.